Caminhos que levaram à criação dos bacharelados interdisciplinares no Brasil - Martins, Nádia de Fátima Borba (2017)
The research analyzes the political-educational context in which graduate courses called Interdisciplinary Bachelors were conceived and created. The bibliographic research was used, with a qualitative approach. As instruments to obtain data that contributed to the analysis of that context, semi-structured interviews were conducted, with two teachers participating in the Working Group, established by the SESu / MEC Ordinance no. 383 of April 12, 2010, which prepared the Guidelines for Interdisciplinary Bachelor's Degree. In order to subsidize the study, the theoretical contribution of theses and dissertations was sought, in which it was decided to use Ball & Bowe's Policy Cycle Approach, specifically regarding the Context of Influence. With the combination of studies on the subject, carried out and disseminated in theses and dissertations, the experiences reported by the interviewees and the authors consulted, it was possible to obtain information that brought some light on the paths that led to the creation of the Graduation Courses called Interdisciplinary Bachelors. These paths are certainly due to the transformations resulting from globalization in all areas and in particular in the field of educational policies. . On the other hand, in seeking to identify the paths that led to the creation in Brazil of undergraduate courses called Interdisciplinary Bachelor's, one can affirm that this new training proposal reflects a situation that presents itself as a worldwide trend: the reorganization of knowledge in the perspective of interdisciplinary integration, which according to the authors studied, could cause the "frontiers of scientific knowledge" to advance. The Bologna Process, flagship of education reform in Europe, was an inspiration matrix for Brazilian Interdisciplinary Bachelor's. Another inspiring source of the national proposal were the major American colleges and the brief experience of the University of Brasilia in 1961, idealized by Anísio Teixeira and Darcy Ribeiro. Thus, the study, brought some light on the paths that led to the creation of the Undergraduate Courses called Interdisciplinary Bachelor.